MARBOT MASJID DI PEKANBARU (Studi Tindakan Rasional Mahasiswa Menjadi Marbot Masjid di Kecamatan Tampan) - Dian Dwi Rahmayani; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was conducted in the District of Tampan, Pekanbaru City. The purpose of this study was to find out what the reasons are owned by the student to work as mosque marabouts while conducting lectures in District of Tampan Pekanbaru City. The focal point of this study is any reason for a student to work as marabouts mosque in the District of Tampan, Pekanbaru City. This research was conducted in three students who study while working as mosque marabouts by three mosques where the mosque is determined base dont heuse of purposive sampling technique. The study used observation, indepth interview sand documentation. Researchers found that there are several reason sstudents college while working as mosque marabouts is as follows: dueto economic factors, and non-economic, Non-economic form: worship, hobby, researchers found that the subject sofresearch work because they want to be closeto the Almighty, theim pulset olive independently, the researchers found that the study subject swould like to help the economy of his family and also wanted to have an independent attitude. There is a pattern of division of time between the time the subject of research work, college, and recreation as well as the following: the division of the average college research subject canmanage their college studies whilst working so that the research subjects did not neglect their college studies because of their job. The division of time worked, on average, the study subjects did not neglect their work even though they are second priority and their studies are their priorities. The division of recreation time, on average the study subjects have recreation time to relieve their work stress and their college study stress, some of the options of recreation time subjects are hanging out with friends, exercising, rest, playing music, and tour some recreational places. Keywords: College Students, Marabouts, Rational Action.